Muscle Strength and Changes in Physical Function in Women With Systemic Lupus Erythematosus. Issue 8 (August 2015) - Andrews, James S.; Trupin, Laura; Schmajuk, Gabriela; Barton, Jennifer; Margaretten, Mary; Yazdany, Jinoos; Yelin, Edward H.; Katz, Patricia P.
<x xml:space="preserve">Abstract</x> Objective Cross‐sectional studies have observed that muscle weakness is associated with worse physical function among women with systemic lupus erythematosus (SLE). The present study examines whether reduced upper and lower extremity muscle strength predict declines in function over time among adult women with SLE. Methods One hundred forty‐six women from a longitudinal SLE cohort participated in the study. All measures were collected during in‐person research visits approximately 2 years apart. Upper extremity muscle strength was assessed by grip strength. Lower extremity muscle strength was assessed by peak knee torque of extension and flexion. Physical function was assessed using the Short Physical Performance Battery (SPPB). Regression analyses modeled associations of baseline upper and lower extremity muscle strength with followup SPPB scores controlling for baseline SPPB, age, SLE duration, SLE disease activity (Systemic Lupus Activity Questionnaire), physical activity level, prednisone use, body composition, and depression. Secondary analyses tested whether associations of baseline muscle strength with followup in SPPB scores differed between intervals of varying baseline muscle strength. Results Lower extremity muscle strength strongly predicted changes over 2 years in physical function even when controlling for covariates. The association of reduced lower extremity muscle strength with reduced physical function in the future was greatest among the weakest women. Conclusion Reduced lower extremity muscle strength predicted clinically significant declines in physical function, especially among the weakest women. Future studies should test whether therapies that promote preservation of lower extremity muscle strength may prevent declines in function among women with SLE.